Is There Evidence for Myelin Modeling by Astrocytes in the Normal Adult Brain? - Varela-Echevarría, Alfredo; Vargas-Barroso, Víctor; Lozano-Flores, Carlos; Larriva-Sahd, Jorge (Frontiers in Neuroanatomy, 2017)
A set of astrocytic process associated with altered myelinated axons is described in the forebrain of normal adult rodents with confocal, electron microscopy, and 3D reconstructions. Each process consists of a protuberance that contains secretory organelles including numerous lysosomes which polarize and open next to disrupted myelinated axons. Because of the distinctive asymmetric organelle distribution and ubiquity throughout the forebrain neuropil, this enlargement is named paraxial process (PAP). The myelin envelope contiguous to the PAP displays focal disruption or disintegration. Clusters of large, confluent, lysosomes proved to be an effective landmark for PAP identification. In 3D assemblies lysosomes organize a series of interconnected saccules that open up to the plasmalemma next to the disrupted myelin envelope(s). Activity for acid hydrolases was visualized in lysosomes, and extracellularly at the PAP-myelin interface and/or between the glial and neuronal outer aspects. Organelles in astrocytic processes involved in digesting pyknotic cells and debris resemble those encountered in PAPs supporting a likewise lytic function of the later. Conversely, processes entangling tripartite synapses and glomeruli were devoid of lysosomes. Both oligodendrocytic and microglial processes were not associated with altered myelin envelopes. The possible roles of the PAP in myelin remodeling in the context of the oligodendrocyte-astrocyte interactions and in the astrocyte´s secretory pathways are discussed.